Strategi Komunikasi Forum Kerukunan Umat Beragama (FKUB) Aceh dalam Menghadapi Stereotip Intoleran Terhadap Agama selain Islam - Ladayani, Wildia Ulfita; Nur, Hasan Basri M.; Furqany, Syahril (Da'watuna: Journal of Communication and Islamic Broadcasting, 2026)
Aceh is often labeled as an intolerant region towards religions other than Islam. This stereotype of intolerance is very detrimental to Aceh. Because social reality shows that interfaith interactions in Aceh are highly harmonious. This study aims to identify the factors causing such stereotypes and analyze the communication strategies of Aceh’s Interfaith Harmony Forum (Forum Kerukunan Umat Beragama/FKUB) in responding to them. This research uses a descriptive qualitative approach. Data was collected through participatory observation in Banda Aceh City, document analysis, and in-depth interviews with five religious leaders: the Chair of Aceh FKUB (Islam) and respective leaders from Christianity, Catholicism, Buddhism, and Hinduism. The findings indicate that the intolerance stereotype does not stem from empirical experience, but rather is a discursive construction by external actors due to four factors: (1) decontextualized survey methodologies that disregard Aceh’s asymmetric autonomous status; (2) media framing that exaggerates episodic conflicts; (3) misconceptions about the implementation of Islamic Sharia, which in fact only applies to Muslim adherents; and (4) the scarcity of counter-narratives in the national public sphere. In response, Aceh FKUB has developed four strategies: (1) interfaith dialogue; (2) interfaith social participation; (3) persuasive approaches in conflict resolution; and (4) policy advocacy and knowledge production. However, in general, these strategies remain micro-scale and reactive. The study recommends the establishment of a narrative task force by the Aceh Government and Aceh FKUB, as well as collaboration with young content creators to build evidence-based counter-narratives as a form of counter-labelling.